The moderating effect of self-control in the relationship between trait anger and negative affectivity on workplace bullying: a study among nurses in Jordan - Abuseif, Sami; Chew Abdullah, Nor Azimah (IISTE, 2016)
The workplace bullying phenomenon is widespread and negatively impacts individuals and organizations. Several studies have reported the negative implications of bullying behavior in the workplace that can damage the workers’ health and affect their level of performance. Previous researches in management and organizational psychology sciences have indicated that workplace bullying is related to individual variables, such as trait anger and negative affectivity. However, they have revealed inconsistent results.Thus, a moderating variable is proposed.The purpose of this paper is to investigate the moderating role of self-control on the relationship between trait anger and negative affectivity on workplace bullying. Data were collected using a questionnaire distributed to 273 nurses from five private hospitals in Amman, Jordan.The data analysis reveals a significant relationship between trait anger and workplace bullying. In addition, the findings show that self-control moderates the relationship between trait anger and workplace bullying.